Disaster, Displacement and Rehabilitation A Case Study of Kosi Floods in North Bihar - Gangwar, Sneh; Thakur, Baleshwar (National Geographical Journal of India, 2022)
The Kosi river, also called as the sorrow of Bihar, is notorious for flood. It causes devastating flood killing thousands of life and destroying property in billions. Many steps taken by the government to control flood of the Kosi river has been unsuccessful, as the river is known for changing its courses. In 2008, the river Kosi completely changed its course inundating areas which was supposed to be safe from floods. The flood of 2008 killed more than 50 thousand people and many more became displaced and homeless. Displaced people had to face various problems like lack of livelihood, loss of house and property, lack of health and hygiene, increase in violence etc. Post flooding, because of constrained livelihood opportunities, depressed economy and probability of future flooding event, many families have migrated to other parts of the country and many of the affected communities displaced from their land for long time. This study focuses on the extent of displacement caused by disasters in India as well as magnitude of displacement caused by Kosi flood 2008 and the government response for recovery and rehabilitation of the displaces. For this purpose, the satellite images of study area (North Bihar) were taken and the extent of flood and its impacts on the area were studied. For the analysis, data is compiled from field surveys and secondary sources, which give basic information on the problem. Data is also collected from different organizations and NGOs in the form of statistical tables, maps and reports. They have been used to understand the experiences of displaces and to evaluate the rehabilitation in the area after Kosi flood 2008